The effect of adding ytterbium trifluoride on the radiopacity, compressive strength, setting time and bioactivity of biodentine: an in vitro study - Bahaa, Nareman Mahmoud; El-Korashy, Dalia Ibrahim; Sherief, Dalia Ibrahim (Brazilian Dental Science, 2022)
Objective: This study aimed to evaluate the radiopacity, compressive strength, setting time and bioactivity of Biodentine after modification with Ytterbium Tri-Fluoride (YbF3) in three different concentrations. Material and Methods: Radiopacity was determined using the equivalence in millimeters of aluminum (mm Al) from digital radiographs. Compressive strength was evaluated using a universal testing machine. The initial and final setting times were evaluated using Gillmore needle. The bioactive potential was evaluated using the environmental scanning electron microscope (ESEM) connected with Energy Dispersive X-ray analysis (EDX) and X-ray Diffractometer (XRD) at three different time intervals. pH was measured using a pH-meter. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc tests (P< 0.05). Results: Radiopacity of Biodentine with 2.5%, 5% and 7.5% YbF3 was significantly higher than unmodified Biodentine (P < 0.05). Unmodified Biodentine showed the highest mean compressive strength values compared to all other groups (p< 0.05). The addition of YbF3 to Biodentine has extended the final setting time except for the 2.5% YbF3 group that showed no significant difference compared to the control. All groups showed an alkaline pH at 28 days, ESEM coupled with EDX analysis showed evidence of dense globules of calcium phosphate on the surface indicating enhancement of bioactivity. Conclusion: 2.5% YbF3 can be a promising radiopacifying agent to Biodentine with improvement in radiopacity, bioactive potential and maintaining the setting time and compressive strength at acceptable level as indicated by the ISO standards. KEYWORDS Ytterbium trifluoride; Radiopacity; Biodentine; Bioactivity.